2020
DOI: 10.3390/jcm9051521
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in Pregnancy: A Comprehensive Summary of Current Guidelines

Abstract: Since the declaration of the global pandemic of COVID-19 by the World Health Organization on 11 March 2020, we have continued to see a steady rise in the number of patients infected by SARS-CoV-2. However, there is still very limited data on the course and outcomes of this serious infection in a vulnerable population of pregnant patients and their fetuses. International perinatal societies and institutions including SMFM, ACOG, RCOG, ISUOG, CDC, CNGOF, ISS/SIEOG, and CatSalut have released guidelines for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
114
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(123 citation statements)
references
References 4 publications
0
114
0
6
Order By: Relevance
“…For this reason governments have taken precautions like lockdown, social distancing, compulsory use of personal protective equipments and comprehensive regulations in healthcare policies [ 2 ]. Moreover, health authorities all over the world have prepared guidelines and management protocols to control the disease [ 3 ]. On the other hand, no consensus has been reached on the optimal COVID-19 screening policy, procedure specific precautions for healthcare workers and treatment modalities for infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason governments have taken precautions like lockdown, social distancing, compulsory use of personal protective equipments and comprehensive regulations in healthcare policies [ 2 ]. Moreover, health authorities all over the world have prepared guidelines and management protocols to control the disease [ 3 ]. On the other hand, no consensus has been reached on the optimal COVID-19 screening policy, procedure specific precautions for healthcare workers and treatment modalities for infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large and rapidly rising number of cases of COVID-19, data concerning clinical characteristics of pregnant women with the disease are limited [9]. The aim of this study was to evaluate the laboratory characteristics of pregnant women with SARS-CoV-2 infection compared to infected non-pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of care guidelines from international perinatal societies and institutions found that most either recommended no visitors or one asymptomatic support person, and expedited discharge was recommended by the American College of Obstetrics and Gynecology, the Catalan Health Service, and the Society for Maternal and Fetal Medicine. 37…”
Section: Labor and Deliverymentioning
confidence: 99%